X-ray Characteristics of the Hot Stars in Trumpler 14 and 16. - Bilty, Kati (My University, 2009)
We have obtained X-ray data from the orbiting Chandra X-ray observatory in order to investigate the hot stars in the star clusters Trumpler 14 and 16. Our data set contains a number of CCD images centered on two stars in the clusters (HD93250 and HD93129). After combining our images into a master image, a major initial task was determining which sources were detected and identifying them with previously cataloged optical sources. The dimmest sources have resulted in only a handful of photon counts and are therefore at the edge of detection for the instrument, making these detections difficult. The images of the brightest stars have resulted in thousands of photon counts.
Color poster with text, images, and charts (Spring 2009)
Keywords: Early stars--Spectra; Spectral irradiance--Measurement; Photons--Measurement; Posters